Aboriginal identity and the ontology of culture - Risk, Meredith (University of Guelph, 1998)
This thesis is an investigation of Aboriginal self-representation. Anthropological literature on identity and authenticity is examined and used to argue that 'culture', which has been deconstructed by some anthropologists, is the very concept upon which many of these self-representations are based. This phenomena is studied 'in action'--at a site of identity--presentation of First Nations peoples. Interviews with visitors to this site are also conducted, in order to gain information about the reception of this identity. The site chosen is the Woodlands Cultural Centre in Brantford, Ontario, where interviews were conducted with staff members as well as tourists visiting the on-site museum, and Niagara College teachers who participated in a workshop led by staff of the W.C.C. Common themes from these interviews are highlighted, and placed in the context of the anthropological literature on culture and identity. Finally, it is argued that, underlying both the interviews with tourists and teachers and the anthropological literature, there is a fundamental confusion and insecurity about the ontological status of 'culture'.